Regulating the interfacial charge transfer and constructing symmetry‐breaking sites for the enhanced N2 electroreduction activity. Issue 2 (2nd September 2022) - Zhang, Xiaoxue; Cao, Yuehan; Huang, Zhen‐Feng; Zhang, Shishi; Liu, Chengguang; Pan, Lun; Shi, Chengxiang; Zhang, Xiangwen; Zhou, Ying; Yang, Guidong; Zou, Ji‐Jun
Abstract: The Haber–Bosch process for industrial NH3 production is energy‐intensive with heavy CO2 emissions. Electrochemical N2 reduction reaction (NRR) is an attractive carbon‐neutral alternative for NH3 synthesis, while the challenge associated with N2 activation highlights the demand for efficient electrocatalysts. Herein, we demonstrate that PdCu nanoparticles with different Pd/Cu ratios anchored on boron nanosheet (PdCu/B) behave as efficient NRR electrocatalysts toward NH3 synthesis. Theoretical and experimental results confirm that the highly efficient NH3 synthesis can be achieved by regulating the charge transfer between interfaces and forming a symmetry‐breaking site, which not only alleviates the hydrogen evolution but also changes the adsorption configuration of N2 and thus optimizes the reaction pathway of NRR over the separated Pd sites. Compared with monometallic Pd/B and Cu/B, the PdCu/B with the optimized Pd/Cu ratio of 1 exhibits superior activity and selectivity for NH3 synthesis. This study provides new insight into developing efficient catalysts for small energy molecule catalytic conversion via regulating the charge transfer between interfaces and constructing symmetry‐breaking sites. Abstract : Cu acts as an efficient electron‐donating promoter, which could form Pd–Cu symmetry‐breaking interfacial sites with electron‐rich environments to tune the adsorption mode of N2 from the parallel adsorption over individual metal sites to end‐on adsorption. As expected, the Pd1 Cu1 /B with the optimized Pd/Cu ratio of 1 exhibits excellent activity and selectivity for NH3 synthesis.